EMPOWERING ENTREPRENEURS THROUGH WAQF: A SYSTEMATIC REVIEW - Kamaruzaman, Nur Rasyidah; Ishak, Muhammad Shahrul Ifwat (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Waqf, a foundational element of Islamic social finance, has increasingly attracted scholarly interest for its potential role in supporting entrepreneurship. Traditionally focused on sectors such as education and healthcare, waqf is now being reimagined as a productive instrument to empower micro and small entrepreneurs, particularly those excluded from conventional financing. However, the implementation of waqf-based entrepreneurial initiatives remains limited. This study aims to systematically examine previous scholarly research to consolidate existing knowledge and highlight emerging areas for future study. Guided by the PRISMA framework, this study conducted a systematic review of journal articles published between 2021 and 2025. Articles were sourced from the Scopus and Web of Science databases, resulting in 31 studies deemed relevant. The analysis reveals three overarching themes: (1) Integrating waqf and Islamic social finance for entrepreneurial support, (2) Governance and institutional support for waqf-based entrepreneurial empowerment, and (3) Harnessing waqf for entrepreneurial empowerment and socioeconomic sustainability. The findings indicate a growing number of innovative models, including hybrid financing structures that integrate waqf with instruments such as zakat and crowdfunding, and embed them with Shariah-compliant contracts. However, challenges persist in areas such as public awareness, governance frameworks, and regulatory coordination. Overall, this study highlight the transformative capacity of waqf to advance financial inclusion and foster entrepreneurial development through its strategic integration within the broader Islamic social finance system. It also emphasizes the importance of stakeholder collaboration and further empirical research to institutionalise waqf as a sustainable support mechanism for entrepreneurs. This study enriches the discourse on Islamic social finance by providing valuable insights to inform policy formulation, practical applications, and future scholarly research.